MPLS-enabled applications : emerging developments and new technologies - Minei, Ina (J. Wiley & Sons, 2008)
"Multiprotocol Label Switching (MPLS) is now considered the networking technology for carrying all types of network traffic, including voice telephony, real-time video, and data traffic. In MPLS-Enabled Applications, the Second Edition, the authors methodically show how MPLS holds the key to network convergence by allowing operators to offer more services over a single physical infrastructure. The Second Edition contains more than 150 illustrations, new chapters, and more coverage, guiding the reader from the basics of the technology, including signaling protocols, traffic engineering and fast reroute, though all its major applications." "MPLS Enabled-Applications, Second Edition, contains comprehensive up-to-date coverage of: the current status and the future potential of all major MPLS applications, including L3VPNs (Layer 3 Virtual Private Networks), L2VPNs (Layer 2 Virtual Private Networks), pseudowires and VPLS . (Virtual Private LAN Service); extensive discussion of multicast support over MPLS, including a new chapter dedicated to multicast in VPNs, explaining both the PIM/GRE (Protocol Independent Multicast / Generic Routing Encapsulation) and the next generation BGP/MPLS solutions, new material on support of multicast in VPLS, a much-expanded chapter on MPLS multicast and a section perations and management (OAM) tools for point-to-multipoint LSPs; a new chapter on MPLS in access networks, as well as coverage of the use of MPLS in mobile and data communication networks; interoperation of LDP(Label Distribution Protocol) and BGP (Border Gateway Protocol) based VPLS; comprehensive coverage of the base technology, as well as the latest IETF drafts."--Jacket